PENGUJIAN EMPIRIS ATAS AUDIT DELAY PADA PERUSAHAAN PERBANKAN GO PUBLIC DI BEI JAKARTA TAHUN 2005-2009 - Anike Wulansari; Supriyati . (Universitas Hayam Wuruk Perbanas, 2012)
It is noted that the delay of any information will attract some negative reaction because it would be useless. The objective of this study is to analyze the influence of profitability, profit and loss, auditor opinion, public accountant size, auditor previous opinion, going concern and company size towards the audit delay in banking companies that have been listed in Jakarta Stock Exchange, Indonesia in 2005 until 2009. This research used census method on the companies that have been listed in Jakarta Stock Exchange. The analysis of hypothesis is using Multiple Regressions. Prior to hypothesis test, normality of the data test was done using kolmogorof-Smirnov test. The result of multiple regression model shows that audit delay was influenced by profitability and auditor previous opinion, with the significance at 10%. Yet, profit and loss, public accountant size, auditor opinion, company size and going concern were not significant factors. Based on such results, it is recommended that the auditor should increase the effectiveness and efficiency of his audit performance and, for all existing studies; they should contribute to the current literature on Auditing.